Gusdurian Islamic Social Movement: Political Discourse, Resource Mobilization, and Framing - Nasrudin Nasrudin; Sudiro Sudiro (International Journal of Social Science and Religion (IJSSR), 2022)
Gusdurian network of Islamic social movements covers political discourse, resource mobilization, and movement framing. This movement started from critical-transformative of Islamic thinking to encourage social change in post-reform Indonesia. With the social dynamics after 1998 reform, the social movement of Gusdurian strive to find new breakthroughs to strengthen democratization, pluralism, and religious freedom in Indonesia. The Gusdurian social movement in encouraging religious social change takes advantage of political dynamics, optimizes resources, and frames them in various forms. The findings in this study show that the Gusdurian as a medium for Islamic social movements is a unique phenomenon containing young activists who continue and fight for what Gus Dur has fought for as a religious and national figure.